2000
DOI: 10.1017/s002966510000029x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and other influences in childhood as predictors of adult obesity

Abstract: It has been proposed that there are critical periods during childhood that influence the development of obesity, including gestation and early infancy, the period of adiposity rebound that occurs between ages 5 and 7 years, and adolescence. Despite an extensive literature, there is to date only modest evidence for most of the factors such as nutrition, physical activity and other behavioural factors that are suspected as playing a role in the development of obesity. A recent review of this evidence (Parsons et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
85
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 37 publications
5
85
1
2
Order By: Relevance
“…Brazilian studies found a direct association between childhood socioeconomic status and BMI in late adolescence and early adulthood in men 24,25 , and an inverse association in women 44 . Thus, although the results of cross-sectional studies are subject to reverse causality -whereby obesity can determine current socioeconomic status rather than vice-versa 4,6,8,28,30 -, the transition process described above is consistent with our finding of clearer associations in women than in men for the effects of early poverty. This long-term effect on abdominal obesity appears not to result only from persisting socioeconomic adversities in adulthood, since based on the results of the present review, current socioeconomic status was a partial mediator in the associations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Brazilian studies found a direct association between childhood socioeconomic status and BMI in late adolescence and early adulthood in men 24,25 , and an inverse association in women 44 . Thus, although the results of cross-sectional studies are subject to reverse causality -whereby obesity can determine current socioeconomic status rather than vice-versa 4,6,8,28,30 -, the transition process described above is consistent with our finding of clearer associations in women than in men for the effects of early poverty. This long-term effect on abdominal obesity appears not to result only from persisting socioeconomic adversities in adulthood, since based on the results of the present review, current socioeconomic status was a partial mediator in the associations.…”
Section: Discussionsupporting
confidence: 87%
“…The arrows in the figure indicate the possible causal mechanisms. The most distal determinant is the inheritance of genetic characteristics, which supposedly affects the model's other components, including intra-gestational maternal adiposity, as well as the child's intrauterine and post-natal life 3,23,28 . Genetic load can also influence the parents' socioeconomic status, as in the case of discrimination against black 29 or obese individuals 30 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social-ecological models have been developed allowing an understanding of potential contributing factors impacting on both activity (16) and nutrition (17) . There appear to be critical periods in childhood where adverse factors are associated with higher levels of adult morbidity and mortality, and these may present opportunities for positive intervention (18)(19)(20) .It has been argued that a comprehensive throughschool programme in partnership with health promotion services, with curricular, co-curricular and extracurricular elements, would be more likely to succeed. Interventions in both the school setting and the family setting have been proposed, and single-intervention trials in both settings have been evaluated with limited success (21) .…”
mentioning
confidence: 99%
“…Social-ecological models have been developed allowing an understanding of potential contributing factors impacting on both activity (16) and nutrition (17) . There appear to be critical periods in childhood where adverse factors are associated with higher levels of adult morbidity and mortality, and these may present opportunities for positive intervention (18)(19)(20) .…”
mentioning
confidence: 99%